Prospective evaluation of clinical symptoms of chemotherapy‐induced oral mucositis in adult patients with acute leukemia: A preliminary study - Yeon‐Hee Lee (Clinical and Experimental Dental Research, 2020)
Abstract Objective The objective of this study was to prospectively evaluate the clinical features of chemotherapy‐induced oral mucositis (CIOM) in adult patients with acute leukemia and the aggravating factors for such symptoms. Subjects Thirty‐seven prospective patients aged ≥19 years with acute leukemia undergoing chemotherapy were enrolled. Oral and clinical investigations were performed at baseline and on Day 14 after starting chemotherapy. The presence and severity of cancer‐induced oral mucositis were demonstrated using the World Health Organization (WHO) scoring system. Results On Day 14, we found that oral mucositis had developed in eight patients (21.6%). Hematopoietic stem cell transplantation (HSCT) in patients was a predictor of increased WHO scores (β = 1.937, p < .001). Regarding oral sites, ventral tongue (β = 1.670), soft palate (β = 1.242), and buccal mucosa (β = 0.593) were predictors for increased scores. In addition, the increase in WHO scores was positively correlated with the number of oral lesions (r = .521), the difficulty in eating (r = .250), and the overall oral health (r = .534; all p < .05). Conclusion The main factors affecting the severity of CIOM symptoms were the treatment with HSCT and the location of oral lesions. The incidence of CIOM and WHO scores were not significantly different between the subgroups of disease. Our findings will help clinicians investigate the oral findings after chemotherapy in adult patients with acute leukemia.